Toward a Knowledge Context Report on the First Annual U.C. Berkeley Forum on Knowledge and the Firm - Cohen, Don (California management review)
At the U.C. Berkeley Forum on Knowledge and the Firm, leading academics and knowledge practitioners from Japan, the U.S., and Europe discussed their understandings of organizational knowledge and how firms can influence its creation and use. The meeting brought to the surface a diversity of goals, assumptions and vocabularies-most notably a contrast between the aim of nurturing the process of knowledge creation and that of managing and measuring knowledge use. By exploring both common ground and differences, participants began to weave a knowledge context : a fabric of varied and mutually illuminating ideas about knowledge. Given the complexity of knowledge, this kind of rich context should provide a better framework for answering questions about how to approach and value knowledge work than any single point of view could provide.